(untitled) (Research, Society and Development, 2023)
Objective: To identify the important variables to compose an interdisciplinary assessment of the person with severe COVID-19 and thus develop a bundle. Methodology: This is a qualitative study of the integrative review type. The following databases were searched: Science Direct, Scientific Electronic Library Online, Latin American and Caribbean Literature on Health Sciences, Scopus and Web of Science. Inclusion criteria included studies that addressed the study theme and were available for full-text reading. Duplicates were excluded. Results: Nine articles were selected for full-text reading. The studies served as a basis for the creation of the assessment instrument for people with severe COVID-19, where the variables were included by means of information extracted from the review, such as: calorie needs, stimulated mobility and oral hygiene. Final considerations: It is believed that the insertion of an instrument such as this in clinical practice can collaborate with the collection of important information for interdisciplinary discussion in a continuous and updated way.